A quantitative fluorescence‐based steady‐state assay of DNA polymerase. (10th March 2014) - Driscoll, Max D.; Rentergent, Julius; Hay, Sam
<x xml:space="preserve">Abstract</x> Fluorescent dyes that bind DNA have been demonstrated as a useful alternative to radionucleotides for the quantification of DNA and the in vitro measurement of the activity of DNA polymerases and nucleases. However, this approach is generally used in a semi‐quantitative way to determine relative rates of reaction. In this report, we demonstrate a method for the simultaneous quantification of DNA in both its single‐strand and double‐strand forms using the dye PicoGreen. This approach is used in a steady‐state assay of DNA polymerase Klenow fragment exo−, where we determine kcat and Km values for the DNA polymerase that are in excellent agreement with literature values.